Development and Validation of an AI-TPACK Instrument for Pre-Service Elementary Teachers in Mathematics Learning - ERNAWATI ERNAWATI; Muh Alka (Celebes Journal of Elementary Education, 2026)
This study aims to develop and validate an AI-TPACK instrument for pre-service primary school teachers in mathematics learning. The research employed a Research and Development (R&D) design using the 4D model, consisting of define, design, develop, and disseminate stages. The participants were students of the Primary School Teacher Education Program who had taken mathematics learning courses. Data were collected through expert validation forms and instrument trial questionnaires, and were analyzed using content validity, construct validity, reliability testing, and item analysis. The findings indicated that the developed AI-TPACK instrument demonstrated good content validity, adequate construct validity (KMO = 0.86; factor-loading range = 0.54–0.83) , and high reliability (Cronbach’s alpha = 0.92). The instrument is considered feasible for measuring pre-service primary school teachers’ competence in integrating artificial intelligence, pedagogy, technology, and mathematical content in instructional practices. Therefore, the instrument may serve as a valid and reliable tool for research and instructional evaluation in strengthening teacher competencies in the digital era